2018
DOI: 10.1038/s41525-018-0068-1
|View full text |Cite
|
Sign up to set email alerts
|

Complex genetics of female fertility

Abstract: Variation in reproductive lifespan and female fertility have implications for health, population size and ageing. Fertility declines well before general signs of menopause and is also adversely affected by common reproductive diseases, including polycystic ovarian syndrome (PCOS) and endometriosis. Understanding the factors that regulate the timing of puberty and menopause, and the relationships with fertility are important for individuals and for policy. Substantial genetic variation exists for common traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 106 publications
2
37
0
Order By: Relevance
“…For instance, prevalence of infertility may reach 16% 2 and 15% 3 in humans and beef female calves, respectively. Similar to what has been observed in humans 4 , the genetic architecture of fertility in beef heifers is very complex 5,6,7,8,9,10,11,12 . In line with this complexity, female reproductive traits have low heritability.…”
Section: Introductionsupporting
confidence: 72%
“…For instance, prevalence of infertility may reach 16% 2 and 15% 3 in humans and beef female calves, respectively. Similar to what has been observed in humans 4 , the genetic architecture of fertility in beef heifers is very complex 5,6,7,8,9,10,11,12 . In line with this complexity, female reproductive traits have low heritability.…”
Section: Introductionsupporting
confidence: 72%
“…Ultimately, sterility is a multifactorial problem. Many interfering factors can modulate the conception probability (including tubal dysfunction, body mass index, lifestyle) 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The etiopathogenesis of endometriosis is still undefined and debated. To better understand the mechanism leading to the development of endometriosis as a disabling disease instead of spontaneous resolution of peritoneal implants, genetic studies offer an approach of paramount importance [3,220,221,222]. The evidence for a genetic contribution to the development of endometriosis comes from epidemiological studies that reported familial aggregation of the disease in humans [223,224,225,226,227] and primates [228].…”
Section: The Genetics Of Endometriosismentioning
confidence: 99%